REFLECTIONS ON THE TREATMENT RESERVED BY THE BRAZILIAN STATE FOR INDIGENOUS PEOPLES: THE TUPINAMBÁ PEOPLE OF OLIVENÇA - Da Veiga Alves, Denise; Cupsinski, Adelar (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
In the same way that, historically, non-Indigenous people based their relationships with Indigenous peoples on the exploitation and destruction of the natural resources present in their habitat, as well as on their submission and physical and symbolic annihilation, this type of colonizing relationship persists in contemporary times. As used in this article, the word "genocide" comes from BELTRÁO. It means actions that have destroyed and are still destroying indigenous peoples by putting them in villages, directories, indigenous colonies, or indigenous posts set up by the Indian Protection Service (SPI) and later by the National Indian Foundation (Funai). These actions keep them from living on their own land and having children the way they did before the invaders came, and they have been doing this continuously from the colonial era to the present day, taking away their freedom despite a long history of struggles. This means that when the government doesn’t do what it’s supposed to do according to Article 231 of the Federal Constitution—which says that the Union should define traditionally occupied lands, protect and ensure respect for all the assets of indigenous peoples, as well as recognize their social organization, customs, languages, beliefs, and traditions—it’s another cruel form of genocide, leaving these people open to more violence from outsiders or the government itself. This article juxtaposes the relationship between national society and the Brazilian state with the history of the Tupinambá people of Olivença, emphasizing their persistent resistance against attacks and criminalization. Cacique Babau Tupinambá from the Serra do Padeiro village, Rosivaldo Ferreira da Silva, asserts that "genocide is permanent."